MESOPOROUS AEROGEL OF ARENGA PINNATA ENDOSPERM AND THEIR APPLICATION TO ADSORB VITAMIN E FROM PALM FATTY ACID DISTILLATE - TARIGAN, JULIATI BR.; BARUS, DIANA A.; ANGIN, SABARMIN PERANGIN; SEBAYANG, FIRMAN; -, MISDAWATI (International Journal of Applied Pharmaceutics, 2020)
Objective: The mesoporous aerogel (MA) has been produced from Arenga pinnata endosperm (APE) and was used to adsorb vitamin E from palm fatty acid distillate (PFAD). Methods: The adsorption process was carried out through the alcogel stage, followed by drying under dry air and reduced pressure. In the present work response surface methodology based on Box-Benhken design experiment was used to investigate the effect of dry APE types (1–3), the concentration of APE (1–1.5%, wt./v) and solvent exchange time (12–36 h). Results: Based on the result, the optimum parameter to produce aerogel with low-density value are as follows: APE type of 1 with a concentration of 1.5% (wt./v) and 48 h solvent exchange time. The MA occurred from this parameters has diameter of 3.142–3.212 nm. The surface morphology of MA had changed from roughly hollowed to smooth and the amorf intensity decreased after vitamin E adsorption process. Conclusion: The APE aerogels could adsorb vitamin E because the pores of aerogels and the galactomannan as the main component contains the branches galactose, which have hydrophilic phase and mannose which have hydrophobic phase, therefore, hydrophobic vitamin E are easy adsorbed on aerogels.